Occurrence of Fusarium Species and Determination of Their Toxins From Poultry Feeds During Storage - Youssuf A. Gherbawy; Abdullah Altalhi; Pet Ioan; Eman G. A. M. El‐Dawy (International Journal of Microbiology)
At a global scale, grains and poultry feeds are the primary sources of feed. Due to their considerable significance, any fungi capable of infecting these feedstuffs can pose a threat to both food safety and security. Fusarium spp. are a highly significant group of organisms. Fumonisins (FBs), deoxynivalenol (DON), trichothecene (T-2), and zearalenone (ZEN) are classifications of mycotoxins that are synthesized by Fusarium species. Their presence is associated with a range of factors that occur during growth, processing, and storage. We have recorded the high occurrence of Fusarium spp. in grains and poultry feeds in all tested samples. Fusarium (F) oxysporum was the most common species that appeared in all tested two hundred samples. FB1 was the predominant toxin that appeared with the highest concentration in 56 pellet samples with the range of 10.34–1043 μg/kg. Also, it occurred with levels of 4.67–956 μg/kg in the tested ingredients samples. Fusarium verticillioides isolates were the highest producers of FB1. Fusarium spp. isolates showed positive FB1 production with 84.6%, 82.5%, 82.2%, and 78.1%, isolated from pellet feed samples that were collected from Alhassa, Jeddah, Qassim, and Riyadh, respectively. 31.6%, 76.9%, 23.1%, 83.3%, and 88% of tested Fusarium spp. strains exhibited FB1 production in samples of barley, corn, sorghum, soybean, and wheat bran, respectively, with the range of 18–655 μg/kg. Genes responsible for FB1, DON, T-2, and ZEN production were detected in the Fusarium spp. isolates.